Answer:
0
(1/3)x+13/3
5
Explanation:
1. Like any function, g takes numbers from it's domain (-8, -3, 0, 7), and transforms them into numbers in it's range (8, 6, -3, 3). g^-1, it's inverse, maps back from the range into the domain. Since g maps 0 onto -3, g^-1 must turn -3 back to 0
g(0)=-3 == g`(-3)=0
2. To find the inverse of h, let h(x)=y.
Now, y=3x-13
Remember that the inverse maps from the range (the y values) back to the domain (the x's), We want the function that takes a y and turns it into an x. For this, we must solve for x.
From above, y/3+13/3=x
Now that we rearranged h, we must flip the x and y to get the inverse. This happens because the range of h acts as the domain for h^-1
3. The function h will turn 5 to some unknown number. Let's call it w. Then, if you pass w to h^-1, it will be turned back to a 5.
This is equivalent to computing the functions in the reverse order, or writing the composite, which results in x=y, and then computing